Investigating causes and extent - (:unkn) unknown (Publications Office of the European Union, 2016)
"This volume looks at quantitative data to understand better the extent of early leaving from VET (ELVET). It analyses mechanisms for monitoring early leaving (at national and EU-levels), and examines VET and labour-market-specific factors, as well as those related to the individual and his/her family background, contributing to this phenomenon. It aims to assist national policy-makers and decision-makers at different levels in developing existing monitoring systems to measure ELVET and inform VET policies to tackle ELET. It also aims to assist European stakeholders to refine the EU indicator to capture the important variations in individual situations of early leavers. The second volume reviews VET-related measures to tackle ELET, either by preventing learners dropping out and/or by bringing those who have already left back to education and training." (Editor, BIBB-Doku)
Keywords: G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); G 1.3.3 Bildungs- & Erwerbsbiografien; Ausbildungsabbruch; Ursache; Einflussfaktor; Begriff; Ausbildungsabbrecher; Monitoring; Internationaler Vergleich; Quantitative Angaben; Europäische Union